Elevated CD54 Expression Renders CD4+ T Cells Susceptible to Natural Killer Cell-Mediated Killing. (21st August 2019) - Chen, Xi; Chen, Huihui; Zhang, Zining; Fu, Yajing; Han, Xiaoxu; Zhang, Yue; Xu, Junjie; Ding, Haibo; Cui, Hualu; Dong, Tao; Shang, Hong; Jiang, Yongjun
Abstract: Background: Natural killer (NK) cells are an important type of effector cell in the innate immune response, and also have a role in regulation of the adaptive immune response. Several studies have indicated that NK cells may influence CD4+ T cells during HIV infection. Methods: In total, 51 HIV-infected individuals and 15 healthy controls participated in this study. We performed the flow cytometry assays and real-time PCR for the phenotypic analysis and the functional assays of NK cell-mediated deletion of CD4+ T cells, phosphorylation of nuclear factor-κB (NF-κB/p65) and the intervention of metformin. Results: Here we detected high CD54 expression on CD4+ T cells in HIV-infected individuals, and demonstrate that upregulated CD54 is associated with disease progression in individuals infected with HIV. We also show that CD54 expression leads to the deletion of CD4+ T cells by NK cells in vitro, and that this is modulated by NF-κB/p65 signaling. Further, we demonstrate that metformin can suppress CD54 expression on CD4+ T cells by inhibiting NF-κB/p65 phosphorylation. Conclusions: Our data suggest that further studies to evaluate the potential role of metformin as adjunctive therapy to reconstitute immune function in HIV-infected individuals are warranted. Abstract : In this study, a high CD54 expression on CD4 + T cells was found in HIV-infected individuals, and CD54 expression leads to the killing of CD4 + T cells by NK cells. Metformin can suppress CD54 expression by inhibiting NF-κB/p65 phosphorylation.